2021
DOI: 10.1177/0897190021999792
|View full text |Cite
|
Sign up to set email alerts
|

Medication Regimen Complexity Score as an Indicator of Fluid Balance in Critically Ill Patients

Abstract: Background: Critically ill patients are at increased risk for fluid overload, but objective prediction tools to guide clinical decision-making are lacking. The MRC-ICU scoring tool is an objective tool for measuring medication regimen complexity. Objective: To evaluate the relationship between MRC-ICU score and fluid overload in critically ill patients. Methods: In this multi-center, retrospective, observational study, the relationship between MRC-ICU and the risk of fluid overload was examined. Patient demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…24 We assumed homogeneity across medication regimens; however, in practice this may be a highly complex and noisy interaction: therefore, in future work, we seek to utilize Trust Discover platforms to generalize pharmacotherapy pro les that are normalized independent of clinician and institutional bias. 49 Finally, causal inference cannot be assessed by the current study, so it is unknown whether the high mortality observed in Patient Cluster 4 was partly caused by the unique distribution of pharmacophenotypes versus other factors (although notably, Cluster 4 shared similarities among groups). Even with these limitations, this analysis marks the rst time the complete medication pro le has been incorporated into outcomes analysis for ICU patients.…”
Section: Discussionmentioning
confidence: 80%
“…24 We assumed homogeneity across medication regimens; however, in practice this may be a highly complex and noisy interaction: therefore, in future work, we seek to utilize Trust Discover platforms to generalize pharmacotherapy pro les that are normalized independent of clinician and institutional bias. 49 Finally, causal inference cannot be assessed by the current study, so it is unknown whether the high mortality observed in Patient Cluster 4 was partly caused by the unique distribution of pharmacophenotypes versus other factors (although notably, Cluster 4 shared similarities among groups). Even with these limitations, this analysis marks the rst time the complete medication pro le has been incorporated into outcomes analysis for ICU patients.…”
Section: Discussionmentioning
confidence: 80%
“… 32 Notably, positive fluid balance may serve as an “intervenable” patient event during an ICU stay that pharmacists can target and prevent, as diuretics represent a readily available strategy. 33 …”
Section: Discussionmentioning
confidence: 99%
“…32 Notably, positive fluid balance may serve as an "intervenable" patient event during an ICU stay that pharmacists can target and prevent, as diuretics represent a readily available strategy. 33 There are no studies about early diuresis in a septic HF population, and the timing of de-resuscitation remains debated. Though the 2021 Surviving Sepsis Guidelines emphasize 30 mL/kg given within the first 3 hours, much less is known regarding when to initiate diuresis.…”
Section: Discussionmentioning
confidence: 99%
“…The studies that chronicle the development and evaluation of the MRC-ICU are summarized in Supplemental Digital Content -Table 2 (http://links.lww.com/CCM/H141). The primary limitation of all MRC-ICU evaluations to date has been the small sample and one (or two) center designs that inherently lack the robust external validity necessary for widespread use (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…The Medication Regimen Complexity-ICU (MRC-ICU) scoring tool is the first metric proposed with the specific intention of describing relevant relationships in the optimal critical care pharmacy practice model and has shown early promise at overcoming historical limitations in pilot studies (6)(7)(8)(9)(10)(11)(12)(13). This 37-line item score has been provided in Supplemental Digital Content -Table 1 (http://links.lww.com/CCM/H141).…”
mentioning
confidence: 99%